The Digital Efficiency Paradox: Modeling the Trade-off Between Documentation Speed and Patient Interaction in Infrastructure-Limited EHR Ecosystems - Amanda Appiah Acheampong; Samuel Antwi; Josephine Arhin Gordon; Khadijatu Adiss Yusif; Maame Dankwah Tiboah Asare; Richard Peter Yalley; Zainabu Mamley Adams; Abdul-Mumin Musah Bingle; Ramatu Adamu; Muniratu Abdul Razak; Rosemary Abrefa Bermaa; Francisca Tsidih (Universitas Muhammadiyah Semarang Press, 2025)
The digitization of clinical workflows through Electronic Health Records (EHR) is a global imperative aimed at enhancing data accuracy and care coordination. However, in resource-constrained environments, the transition from paper-based systems to digital platforms often surpasses the readiness of existing infrastructure. While systems such as the Lightwave Health Information Management System (LHIMS) in Ghana offer the promise of increased efficiency, they also introduce critical dependencies on unstable power and internet connectivity. This situation creates a